Classroom Action Research on Solving Problems in Janapriya Multiple Campus, Pokhara - Tripathi, Krishna Prasad (AWADHARANA, 2022)
The study on action research on solving classroom problems in Janapriya Multiple Campus (JMC) based on a preliminary study on the solutions of existing problems in the classroom. The objectives of the study were to identify the problems and manage to solve them through various interventions. All the students (62) in class 12 who were studying in the Education faculty of JMC were included in the sample through the census method, where the researcher taught two periods daily. It was done within seventy-five days, half of the academic year after the first lockdown and before the second lockdown, using qualitative research with the interpretive paradigm and narrative research design. The researcher observed the situations, listed the problems seen in the classroom, and conducted two FGDs with five teachers and eight students, respectively. Action research procedures for action research, namely planning, implementing, observing, and reflecting, were implemented, and a theory of change was used to evaluate the interventions. Baseline and end-line evaluations were used to find out the change. The researcher used observations, FGD, and tests to collect data. The data obtained were presented mostly qualitatively and less quantitatively. The findings show that regular attendance and keeping parents informed are effective in improving the attendance of the students. Similarly, the attendance in the alternative period help to solve the bunk of class. Proving questions to students make them more attentive and aware of their class activities. This can be seen from the improvements after each cycle. Each and every cycle help students get some progress in solving problems. It is very useful to maintain good relations among teacher, the students and their parents at the end of the cycle.